Efficacy and outcomes of surgical staples as an alternative to conventional skin closure in canine mastectomy - Fábia Kariny Mendes Moreno; Gabriel Menezes Rodrigues; Victor Otero Martinez; Cinthia Oliveira de Araujo Barreto; Laís Pereira Silva; Thanielle Novaes Fontes; Vivian Fernanda Barbosa; João Moreira da Costa-Neto; Alessandra Estrela-Lima (PLoS ONE, 2025)
Surgical wound closure is critical in oncologic surgeries and directly influences healing, postoperative complications, and recovery time. In canine mastectomies, conventional skin closure with nylon sutures remains the standard technique; however, surgical staples have emerged as a potential alternative that can potentially optimize surgical efficiency and outcomes. This study evaluated the efficacy of surgical staples as an alternative to routine standard suture (nylon) in female dogs undergoing mastectomies. Fifty female dogs were divided into two groups: one was treated with nylon suture (NS group, n = 25) and the other with surgical staples (SS group, n = 25). Surgical time, local wound temperature, and wound healing characteristics were evaluated. Thermographic analysis of the surgical scar was performed on a subsample. Logistic regression and multivariate linear analysis were used to compare differences between the techniques, and an independent samples t test was applied to compare surgical and suture times. No significant differences were found between the groups regarding age, weight, incision size, body size, and reproductive status. Total surgical time was significantly shorter in the SS group (p = 0.011). The closure time was 9.8 times shorter in the SS group versus the NS group (p < 0.001). The average wound temperature was higher in the NS group (p < 0.001). The SS group showed fewer occurrences of wound alterations (p = 0.029) and a lower frequency of focal inflammatory exudate (p = 0.013). The thermographic analysis showed more white pixels and higher temperatures in the surgical wound in the NS group versus the SS group (p = 0.032 and p < 0.001, respectively). Surgical staples were found to be safe and effective for wound closure in mastectomies in female dogs, offering a viable alternative to traditional nylon suture techniques. Although the cost of staples is slightly higher, the benefits of shorter surgical time and reduced complications can make this technique a favorable choice, especially for oncologic patients with additional health concerns or surgical time restrictions.